Is stellar hedge fund performance for real? - KOSOWSKI, Robert (Institutional Knowledge at Singapore Management University, 2005)
We apply a robust bootstrap to evaluate the performance of a large universe of hedge funds. Our bootstrap estimates indicate that the performance of the top hedge funds cannot be attributed to chance alone. This is true even after adjusting for back fill bias, serial correlation, and structural breaks. Also, we find that hedge fund alpha differences persist over three year horizons. However, an investment strategy designed around this will run into difficulties as the persistence is often confined to small funds that are effectively closed to new inflows. Moreover, Bayesian estimates suggest that standard alphas may be overestimated by 41% for the average top fund.